2011
DOI: 10.1123/jpah.8.8.1034
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Workstations: A Worksite Physical Activity Intervention in Overweight and Obese Office Workers

Abstract: The additional PA energy expenditure from using the TMWS favorably influenced waist and hip circumferences and lipid and metabolic profiles in overweight and obese office-workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 40 publications
3
132
1
1
Order By: Relevance
“…22 At follow-up, mean steps/day for the control group remained indicative of the "low active" classification, whereas higher steps/day values among the intervention group can be characterized as "somewhat active" (7500 to 9999 steps/day). 22 Although increases in steps/day were statistically significant, they are substantially less than the 3-month increases in steps/day (median increase of 6111 steps/day) reported in the quasi-experimental treadmill desk trial conducted by John et al 9 Considering average speed on the treadmill was 1.8 miles/hour, observed changes in ambulatory behavior at stepping rates of 40 to 99 steps/minute (purposeful steps, slow walking, and medium walking) are consistent with previous data detailing the relationships between cadence and walking speed, [23][24][25] suggesting that such velocities (less than 2.0 mph) are typically associated with cadences of less than 100 steps/minute. Increases in time spent between 40 and 99 steps/minute seem to be reflective of light physical activity (500 to 1951 activity counts/minute), the only activity count-defined intensity of physical activity that demonstrated a significant differential group change between baseline and follow-up.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…22 At follow-up, mean steps/day for the control group remained indicative of the "low active" classification, whereas higher steps/day values among the intervention group can be characterized as "somewhat active" (7500 to 9999 steps/day). 22 Although increases in steps/day were statistically significant, they are substantially less than the 3-month increases in steps/day (median increase of 6111 steps/day) reported in the quasi-experimental treadmill desk trial conducted by John et al 9 Considering average speed on the treadmill was 1.8 miles/hour, observed changes in ambulatory behavior at stepping rates of 40 to 99 steps/minute (purposeful steps, slow walking, and medium walking) are consistent with previous data detailing the relationships between cadence and walking speed, [23][24][25] suggesting that such velocities (less than 2.0 mph) are typically associated with cadences of less than 100 steps/minute. Increases in time spent between 40 and 99 steps/minute seem to be reflective of light physical activity (500 to 1951 activity counts/minute), the only activity count-defined intensity of physical activity that demonstrated a significant differential group change between baseline and follow-up.…”
Section: Discussioncontrasting
confidence: 59%
“…32 Although there has been a randomized cross-over trial of physician's use of treadmill desks, 12 other interventions have been quasi-experimental in design. [8][9][10] Thus, this study represents the first randomized controlled trial of shared-treadmill desk use among office workers with predominantly seated working assignments. A primary strength of this study is that we tracked each participant's daily use of the treadmill desk in great detail via an electronic reporting system with follow-up inquiries when reports were not submitted.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although several studies have examined the impact of reduced screen-based sedentary behaviours on body weight in children and youth (9,73,74), to date no studies have examined the metabolic impact of reducing total sedentary time in any pediatric population. Similarly, while a small number of studies have examined the impact of reducing total sedentary time in adult populations, most interventions to date have focused on feasibility rather than health outcomes (75)(76)(77)(78)(79)(80)(81)(82). As a result, the efficacy and effectiveness of reducing total sedentary time remains unclear in both pediatric and adult populations.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…While self-reported screen time is consistently associated with increased adiposity and cardiometabolic disease risk in children and youth independent of physical activity levels (7)(8)(9)(10)61,68,70,(73)(74)(75), the relationship between objectively measured sedentary time and health indicators is far less clear. Of the numerous studies examining the relationship between objectively measured sedentary time and markers of adiposity and cardiometabolic disease risk in the pediatric population (5,12,37,64,68,69,71,(74)(75)(76)(77)(78)(79)(80)(81)(82), only a small number (64,69,79) have detected associations which remained significant after adjustment for physical activity ( (70). In contrast, the authors observed no independent associations between accelerometer-derived sedentary time and markers of cardiometabolic risk in the same sample.…”
Section: The Role Of Sedentary Behaviour Modality: Screen Based Vs Nmentioning
confidence: 99%